If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -2 = 10x + -9 Reorder the terms: -2 + 9x = 10x + -9 Reorder the terms: -2 + 9x = -9 + 10x Solving -2 + 9x = -9 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -2 + 9x + -10x = -9 + 10x + -10x Combine like terms: 9x + -10x = -1x -2 + -1x = -9 + 10x + -10x Combine like terms: 10x + -10x = 0 -2 + -1x = -9 + 0 -2 + -1x = -9 Add '2' to each side of the equation. -2 + 2 + -1x = -9 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = -9 + 2 -1x = -9 + 2 Combine like terms: -9 + 2 = -7 -1x = -7 Divide each side by '-1'. x = 7 Simplifying x = 7
| 127+2x+41=180 | | 5t^2-25t+20=0 | | (69.8+x)/7=70 | | 6n+3.30=7.80 | | a=4+1.5y | | 4(2x+1)-x=10 | | 4(a-y)=2y+16 | | 11/5x-6/5 | | x+2x+1+2x-2=110 | | 117+x=180 | | 7(328/25) | | y=x+(1.1*x) | | (x-2)/4=8/(x-6) | | 5-9n=40 | | s/12-5=6 | | 3x(x-6)(2.7x-6)=0 | | (8/11)(n-10)=64 | | s/12-5=67 | | -3m+9=10-3m | | (8-x)+(3-x)= | | sqrt(8x+1)=sqrt(4x+9) | | 0.8(4-g)=5.6g | | 6(-5n+1)+5n=-2n-40 | | 2x-(-2+x)=3 | | 10x+4x^2=66 | | 7/8p-r | | -(-5x+4)= | | -3x-5y=4 | | -y-15y-4y+13y+2y=20 | | -1(1-4x)=-22+x | | k^2+6+5k=0 | | 96-n=-23 |